Asia and the World: “Travelers' Tales” - EAA Editorial Office (Education About Asia, 2021)
International travel is still a dicey prospect for most of us because of the pandemic, but almost all Digest readers probably love travel at some level. The following entries could be vicarious travel for imaginative readers, but each recommended EAA article or essay, in my opinion, helps students and instructors better understand the often profound effects of literal and figurative travelers and ideas impacting different parts of Asia and the world in a variety of ways.
Keywords: Asia General; China; China and Inner Asia; East Asia; History; Japan; Korea; Northeast Asia; Southeast Asia; Vietnam